2014
DOI: 10.3324/haematol.2013.087916
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of induced pluripotent stem cells in chimeric mice with  -thalassemia

Abstract: chimeric murine models to evaluate the in vivo efficacy, safety, and stability of treatment with β hu -β 654 iPSCs (β 654

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…We suggest that the therapeutic effect of FOE-treated fibroblasts would improve if more FOE-treated fibroblasts were transplanted or if purified iMS cells derived from FOE-treated fibroblasts were transplanted. In fact, iPS cells have demonstrated dose-dependent stable therapeutic effects in chimeric mice with beta-thalassemia [17]. Human dystrophin expression in FOE-treated fibroblast-transplanted mdx mice was detected, indicating that reprogrammed cells were present, and such cells expressed multipotent markers, integrated into the injury site, and expressed dystrophin in mice.…”
Section: Discussionmentioning
confidence: 95%
“…We suggest that the therapeutic effect of FOE-treated fibroblasts would improve if more FOE-treated fibroblasts were transplanted or if purified iMS cells derived from FOE-treated fibroblasts were transplanted. In fact, iPS cells have demonstrated dose-dependent stable therapeutic effects in chimeric mice with beta-thalassemia [17]. Human dystrophin expression in FOE-treated fibroblast-transplanted mdx mice was detected, indicating that reprogrammed cells were present, and such cells expressed multipotent markers, integrated into the injury site, and expressed dystrophin in mice.…”
Section: Discussionmentioning
confidence: 95%
“…Human iPSCs obtained from this patient were able to differentiate into hematopoietic cells that synthesized fetal Hb in vitro, thus raising the possibility of using iPSCs to treat patients with homozygous β-thalassemia [42]. vectors set the stage for its application in clinical settings [45]. Cavazzano et al reported one effective case in a phase I/II clinical trial, but several recently published studies showed that these approaches remained rather inefficient [45].…”
Section: Thalassemiamentioning
confidence: 99%
“…vectors set the stage for its application in clinical settings [45]. Cavazzano et al reported one effective case in a phase I/II clinical trial, but several recently published studies showed that these approaches remained rather inefficient [45]. Therapies using iPSCs combined with transgenes can potentially cure thalassemia in the future, but obstacles such as safety, efficacy and cell stability remain to be solved.…”
Section: Thalassemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Combining ex vivo gene transfer with iPSC may have high potential for the treatment of a number of genetic disorders. For example, transducing iPSC with a functional copy of β-globin gene showed promising results both in the treatment of β-thalassemia whether in in vitro ( 51 ) and in in vivo models ( 52 ). However, further studies are needed on this topic as it has been shown that iPSC may implicate some unacceptable safety risks in clinical application.…”
Section: Gene Therapy Medicinal Productsmentioning
confidence: 99%